Role of laterodorsal tegmentum projections to nucleus accumbens in reward-related behaviors - Bárbara Coimbra (Nature Portfolio, 2019)
The laterodorsal tegmental nucleus (LDT) is known to influence reward processing through its projections to the VTA. Here, the authors report that the cholinergic projections from the LDT to the nucleus accumbens play an important role in motivation and positive reinforcement behaviors.